Isotope-geochronological study of Ingozero massive (the Kola Peninsula) - Nitkina, E. A.; Bayanova, T. B. (Vestnik MGTU, 2018)
The Ingozero massive composed of Archeaen gneisses and granitoids is situated in the north-eastern part of the Belomorian mobile belt. The Ingozero massive petrochemical and geochemical characteristics are similar to those of tonalite-trondhjemite-granodiorite (TTG) complexes established on other Archean shields. High concentrations of Na, Ca, and low of K characterize the gneisses of the Ingozero massif and the samples points lie on the tonalite and trondhjemite fields on the Ab-An-Or diagram. The high content of light rare earth elements and the absence of Eu anomalies indicate the origin of rocks from enriched sources without the essential role of fractional crystallization. The isotope U-Pb single zircon grains dating of the biotite gneisses yielded the oldest age for the Ingozero gneisses magmatic protolith at 3 149 ± 46 Ma. Model Sm-Nd ages have shown the formation of the gneisses protolith initial melt occurred at 3.1–2.8 Ga. The ages of metamorphic processes were determined by isotope U-Pb dating (ID TIMS): biotite gneisses – 2 697 ± 9 Ma; amphibolebiotite gneisses – 2 725 ± 2 and 2667 ± 7 Ma; and biotite-amphibole gneisses – 2 727 ± 5 Ma. The ages for granitoids, which cut the deformed gneisses are 2 615 ± 8 Ma and 2 549 ± 30 Ma for plagiogranites and pegmatoid veins in gneisses respectively. Проведено изотопно-геохронологическое изучение биотитовых, амфибол-биотитовых и биотит-амфиболовых гнейсов, а также секущих плагиогранитов и пегматоидных жил Ингозерского массива, расположенного в северо-восточной части Беломорского подвижного пояса и сложенного гнейсами и гранитоидами архея. Петрохимические и геохимические характеристики изученных пород сходны с породами тоналит-трондьемит-гранодиоритовых (ТТГ) комплексов, установленных на других докембрийских щитах. Для исследованных гнейсов Ингозерского массива характерны высокие содержания Na, Ca и низкие K. На диаграмме Ab-An-Or точки химических анализов гнейсов ложатся в поля тоналитов и трондьемитов. Высокое содержание легких редкоземельных элементов и ...